PENERAPAN MODEL ICARE BERBASIS DEEP LEARNING PADA MATERI KALOR UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI SMAN 12 PEKANBARU - Jannah, Nurriyadil; Nasir, Muhammad; Irawan, Dedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
International assessments, such as the International Student Assessment Program, indicate that the quality of education in Indonesia remains below the global average, particularly in science literacy. This condition reflects students' limitations in understanding and applying scientific concepts, highlighting the need for innovative teaching methods to enhance critical thinking and conceptual understanding. One relevant approach is deep learning, which emphasizes meaningful and contextual learning experiences. In physics education, especially on the topic of heat, students often face difficulties due to the abstract and complex nature of the material. Therefore, the ICARE learning model is considered an alternative approach because it provides structured, student-centered stages and can be integrated with deep learning principles. This study aims to analyze student learning outcomes and evaluate the effectiveness of the ICARE model based on deep learning on heat material for eleventh-grade students at SMAN 12 Pekanbaru. The research uses a quantitative quasi-experimental method with a posttest-only control group design. The sample consists of 76 students divided into experimental and control classes. Data were collected through a cognitive test consisting of 25 questions and analyzed using descriptive and inferential statistics, including the Mann-Whitney U test and effect size. The results show that the experimental class achieved higher average scores. The significance value of 0.043 indicates a meaningful difference, with an effect size of 0.23, categorized as small.